Circular RNAs in Intervertebral Disc Degeneration: An Updated Review - Xu, Derong; Ma, Xuexiao; Sun, Chong; Han, Jialuo; Zhou, Chuanli; Wong, Sunny Hei; Chan, Matthew T. V.; Wu, William K. K. (Frontiers in Molecular Biosciences, 2022)
Low back pain (LBP) is a common medical condition that causes severe disability, inflicting huge economical and public health burden. LBP can be attributed to multiple etiological factors, including intervertebral disc degeneration (IDD). Emerging evidence suggested that circular RNAs (circRNAs), a major type of regulatory non-coding RNA, play critical roles in various cell biological processes pertinent to IDD development, including nucleus pulposus cell proliferation and apoptosis as well as extracellular matrix deposition. Increasing number of translational studies also indicated that circRNAs could serve as novel biomarkers for diagnosis and predicting the clinical outcomes of IDD. Our review aims to discuss the recent progress in the functions and mechanisms of newly discovered IDD-related circRNAs.